Mensch sein Fundament, Imperativ oder Floskel? Beiträge zum 10. Internationalen Kongress der Österreichischen Gesellschaft für Philosophie in Innsbruck - Oberprantacher, Andreas; Siegetsleitner, Anne (innsbruck university press, 2017)
The question of what it means and implies to be human is fundamental to both philosophy and society. At the same time, she runs the risk of being answered with phrases. Even today, various questions about humanity are posed: Can humanity be delimited biologically or in its ways of life from other species or artificial creatures? How do people differ from people? Are language ability or free will essential features of being human? These and other questions were discussed intensively during the 10th Congress of the Austrian Society for Philosophy. This anthology presents a selection of contributions.